2017
DOI: 10.1111/ijac.12744
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, friction, and wear properties of Ni‐Al2O3‐MoS2 composite coatings

Abstract: Ni‐Al2O3‐MoS2 composite coatings were prepared on the surface of aluminum alloy substrates by an integrative method of electrophoresis and electrodeposition from the electrolytic solution with different MoS2 concentrations. The surface morphology and compositions of the coatings were studied by scanning electron microscopy equipped with an energy dispersive spectroscope. The microindentation hardness and tribological properties of the coatings were tested using a Vickers hardness tester and friction performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…High incorporation (18.78 wt-%) and uniform distribution of WC particles as well as the smooth and compact morphology of the as-prepared coatings are the primary factors responsible for the wear resistance of the composite coating. The second-phase particles homogeneously dispersed in the coating perform a supporting and bearing role between the friction pairs [31]. Furthermore, some WC particles were separated from the cobalt matrix during the friction and wear test, which changed the friction mode between the friction pairs from sliding to rolling.…”
Section: Resultsmentioning
confidence: 99%
“…High incorporation (18.78 wt-%) and uniform distribution of WC particles as well as the smooth and compact morphology of the as-prepared coatings are the primary factors responsible for the wear resistance of the composite coating. The second-phase particles homogeneously dispersed in the coating perform a supporting and bearing role between the friction pairs [31]. Furthermore, some WC particles were separated from the cobalt matrix during the friction and wear test, which changed the friction mode between the friction pairs from sliding to rolling.…”
Section: Resultsmentioning
confidence: 99%
“…As the WC concentration increases to 35g/L, the phenomenon of low friction coefficient and wear loss could be attributed to the high WC load and compact microstructure of the Co-WC composite coatings. In addition, WC particles uniformly embedded in the Co matrix perform a supporting and bearing role between the friction pairs [15], which avoids the direct contact between the friction surfaces, thereby improving the wear resistance of the Co-WC composite coating. However, if this concentration exceeds the optimal value, many WC particles agglomerate and then incorporate into the cobalt matrix, and these WC agglomerates weaken the bond strength between grains of Co matrix, resulting in a relatively poor wear behavior.…”
Section: Fig 1 Friction Coefficient and Wear Loss Variation Of Co-wc ...mentioning
confidence: 99%
“…The introduction of nanoparticles through PAMAM, polyhedral oligomeric silsesquioxane (POSS) and so on, to design "flexible-rigid" multiscale enhancement structures, achieved synergetic enhancement effect in tribological properties. [21][22][23] It was reported that hyperbranched polyglycerol (HPG) was grafted on carbon fiber surface through anionic ring-opening polymerization to enhance interfacial adhesion. The interfacial and interlaminar shear strength of fiber/epoxy composites modified with HPG enhanced by 90.69% and 49.83%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At present, dendritic polymers were employed to design and construct the interphase for polishing up interfacial compatibility of composites, which had aroused widespread interests. The introduction of nanoparticles through PAMAM, polyhedral oligomeric silsesquioxane (POSS) and so on, to design “flexible‐rigid” multiscale enhancement structures, achieved synergetic enhancement effect in tribological properties 21–23 . It was reported that hyperbranched polyglycerol (HPG) was grafted on carbon fiber surface through anionic ring‐opening polymerization to enhance interfacial adhesion.…”
Section: Introductionmentioning
confidence: 99%